Cerebral Hemodynamic and Neurotrophic Factor Responses Are Dependent on the Type of Exercise - Weaver, Samuel R.; Skinner, Bethany D.; Furlong, Rhodri; Lucas, Rebekah A. I.; Cable, N. Timothy; Rendeiro, Catarina; McGettrick, Helen M.; Lucas, Samuel J. E. (Frontiers in Physiology, 2021)
This study examined acute cerebral hemodynamic and circulating neurotrophic factor responses to moderate intensity continuous exercise (MICT), guideline-based high intensity interval exercise (HIIT) and sprint interval exercise (SIT). We hypothesized that the pattern of middle cerebral artery velocity (MCAv) response would differ between interval and continuous exercise, with SIT inducing the smallest increase from rest, while increases in neurotrophic factors would be intensity dependent. In a randomized crossover design, 24 healthy adults (9 female), performed three exercise protocols: i) MICT (30 min); ii) HIIT (4x4 min at 85% HRmax), and iii) SIT (4x30 s supramaximal). MCAv significantly increased from rest across MICT (Δ13.1±8.5 cm·s-1, p < 0.001) and all bouts of HIIT (Δ15.2±9.8 cm·s-1, p < 0.001), but only the initial bout of SIT (Δ17.3±11.6 cm·s-1, p < 0.001). Immediately following each interval bout, MCAv increased (i.e. rebounded) for the SIT (9–14% above rest, p ≤ 0.04), but not HIIT protocol. SIT alone induced significant elevations from rest to end-exercise in vascular endothelial growth factor (VEGF; Δ28±36%, p = 0.017), brain-derived neurotrophic factor (BDNF, Δ149%±162%, p < 0.001) and greater increases in lactate than in either other protocol (>5-fold greater in SIT, p < 0.001), alongside a small significant reduction at the end of active recovery in insulin-like growth factor 1 (IGF-1, Δ22%±21%, p = 0.002). In conclusion, while the nature of the response may differ, both guideline-based and sprint-based interval exercise have the potential to induce significant changes in factors linked to improved cerebrovascular and brain health.